Early and late aortic propagation velocity values in STEMI patients after successful primary PCI and their relationship with neutrophil to lymphocyte ratio - Yaman, M.; Arslan, U.; Beton, O.; Pamukcu, H. E.; Dogdu, O. (Verduci Publisher, 2016)
OBJECTIVE: Atherosclerosis leads to increased arterial resistance through thickening and stiffening of the arterial wall, a phenomenon largely known as arterial stiffness. M-mode propagation velocity of the descending thoracic aorta, named aortic velocity propagation (AVP) is a novel method for the measurement of the aortic stiffness. We aimed to investigate the difference between early and late values of AVP after successful primary percutaneous coronary intervention (PCI) in ST-elevation myocardial infarction (STEMI) patients. PATIENTS AND METHODS: A total of 103 (70 male, 67.9%) consecutive patients without a previous history of coronary artery disease, who presented with STEMI without hemodynamic compromise and underwent successful primary PCI were enrolled. Transthoracic echocardiography was performed in all patients after primary PCI at 12-24 hour in Intensive Care Unit (early measurements) and three months after the discharge during follow-up (late measurements). Doppler echocardiography, 2D and aortic M-mode propagation velocity measurements were recorded. Haematological and serum biochemical parameters of the study group were recorded. RESULTS: There were no statistically significant differences in 2D echocardiography measurements between early and late evaluations. AVP values increased during 3 months follow-up in all patients. Mean AVP values were 33.7 +/- 11.6 cm/sn and 44.4 +/- 10.5 cm/sn at early and late measurements, respectively (p<0.001). There were significant correlations between differences of AVP and neutrophil-lymphocyte ratio between early and late measurements. CONCLUSIONS: We demonstrated for the first time that AVP values could improve after successful treatment in STEMI patients. The increment in AVP values was closely correlated with a decrement in neutrophil lymphocyte ratio. It can be postulated that AVP has strong correlations with the inflammatory markers.
Keywords: Aortic propagation velocity; STEMI; Primary PCI; Inflammation